Study about Cyber Law of India - Malik, Somia (Innovative Research Thoughts, 2018)
In Simple way we can say that cyber crime is unlawful acts wherein the computer is either a tool or a target or both Cyber crimes can involve criminal activities that are traditional in nature, such as theft, fraud, forgery, defamation and mischief, all of which are subject to the Indian Penal Code. The abuse of computers has also given birth to a gamut of new age crimes that are addressed by the Information Technology Act, 2000.